INCREASING THE STUDENT VOCABULARY SKILL USE FLASHCARD MEDIA THROUGH CHAIN WHISPER GAME IN SEVENTH GRADE OF SMP - Siti Fatimah; Dewi Kurnia Sari (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
The main objective of this study was to determine whether the use of the flashcard method of the chain whisper game technique helps in memorizing and improving English vocabulary. The method used in this study is known as Classroom Action Research (CAR). Data were collected through documentation, observation, field notes, interviews, and tests. The researcher chose class VII, consisting of 24 students, as the subjects in this study. Based on the data obtained, it can be seen that there was a significant increase in students' vocabulary memorization abilities. This is evidenced by the average value of students in the pre-test and post-test 1, which increased from 56.25 to 67.91, or 11.66, while in post-test 1 and post-test 2, it increased from 67.91 to 77.08, or 9.17. This means that the use of the flashcard method through the chain whisper game technique in memorizing vocabulary can improve English vocabulary in class VII students of SMP 2 PGRI Rengas Bekri Lampung Tengah. It can be seen that this study concludes that the technique of memorizing English vocabulary with the chain whisper game can improve the memorization and understanding of class VII students of SMP 2 PGRI Rengas Bekri, Central Lampung, especially students' interest in learning to memorize vocabulary in learning English.